Trade in the Great Sea: The future of EU-Southern neighbourhood trade relations - Jan A. Micallef (European Centre for International Political Economy (ECIPE), 2025)
This policy brief looks into the future of EU-Southern Mediterranean trade relations. It evaluates the current trade and contractual instruments governing these relations and asks if they are sufficient or if more is needed to exploit trade opportunities and manage trade challenges in the region. The policy brief shows why and how the current trade instruments are no longer sufficient. There are two main reasons for this: first, they do not really tackle areas such as services, investment and non-tariff measures (NTMs), all of which are important to unlock economic value for both sides in today's economy; and second, new economic and political developments reinforce the need for better agreements. As trade becomes more political and intertwined with other issues such as energy, critical minerals, the environment and industrial policy, it is necessary to improve the agreements and instruments that govern trade. The policy brief lists some of the upgrades in EU-Southern Mediterranean trade agreements that are necessary. However, it also analyses what challenges there are to pursue these upgrades and what can be done to overcome the problems. The policy brief concludes that working towards these aims will be challenging but not impossible if there is the necessary political will on both sides. Both sides should realise that the price of not doing anything might be higher than the effort that is required to bring their trade instruments up to the standards needed.
Keywords: 330; Außenhandel; Internationale Wirtschaftsbeziehungen; EU-Staaten; EU-Nachbarstaaten; Mittelmeerraum